Management of food cold chains traceability amid the COVID‑19 pandemic - N. A. Gorbunova; V. N. Kornienko (Теория и практика переработки мяса)
The present article considers the functioning of food supply chains and their major component — a continuous cold chain of perishable food products, including meat products, under the conditions of COVID‑19 pandemic. The issues of the impact of the pandemic on production, processing and commercial supply of meat and meat products in Russia and worldwide are being considered. The traceability of temperature fluctuations in meat processing plants is relevant; it becomes an increasingly important factor for efficient logistics to provide the best supply and to keep the food safe in the current conditions. Research data is presented here. The results of the research show that frozen foods serve as carriers and distributors of SARS-CoV‑2 infection without any contact between people. This conclusion highlights additional challenges in controlling the spread of COVID‑19 worldwide, and reveals the mechanism of the disease transmission, taking into account the peculiarities of temperature modes during storage and transportation of perishable meat products. The risks of food cold chains functioning under the conditions of pandemic, the adaptive strategies for their mitigation and logistical systems of tracking are considered, in particular, the application of various data technologies.